THESES OF PSYCHOSOMATIC MEDICINE - F. I. Belyalov (Рациональная фармакотерапия в кардиологии)
The main results of psychosomatic studies are summarized. A high incidence of mental health disorders is shown in patients with somatic diseases. They worsen the prognosis, increase the severity of the condition, make diagnosis and treatment more difficult, reduce the quality of life and work capacity, increase healthcare costs. Antidepressants decrease severity of anxiety and depression, as well as diminish frequency of somatic events and hospitalizations in patients with depression. It is important to take into account the influence of psychotropic drugs on somatic diseases and their treatment. It is important to improve the training of doctors and develop national guidelines for improving the diagnosis and treatment of patients with comorbid somatic and mental diseases.